2011
DOI: 10.2174/138920111796117328
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive PEGylated Liposomes Functionalized With a Fibronectin-Mimetic Peptide Show Enhanced Intracellular Delivery to Colon Cancer Cells

Abstract: pH-sensitive liposomes undergo rapid destabilization under mildly acidic conditions such as those found in endocytotic vesicles. Though this makes them promising drug carriers, their application is limited due to their rapid clearance from circulation by the reticulo-endothelial system. Researchers have therefore used pH-sensitive liposomes that are sterically stabilized by polyethylene glycol (PEG) molecules (stealth liposomes) on the liposome surface. The goal of this study is to bring bio-functionality to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…They are used for delivery of gemcitabine (169) and cisplastin (181). Research has been focused on the development of stealth and targeted pH sensitive liposomes (182). In addition, understanding the polymer backbone structure and resulting hydrophobic behavior can provide very helpful insights into membrane interactions and fusogenic activity of these liposomes (183,184).…”
Section: Preparationmentioning
confidence: 99%
“…They are used for delivery of gemcitabine (169) and cisplastin (181). Research has been focused on the development of stealth and targeted pH sensitive liposomes (182). In addition, understanding the polymer backbone structure and resulting hydrophobic behavior can provide very helpful insights into membrane interactions and fusogenic activity of these liposomes (183,184).…”
Section: Preparationmentioning
confidence: 99%
“…[28] A fibronectin-mimetic peptide (PR-b) has been used to label pH sensitive liposomes for internalization in μ 5 μ 1 expressing cells. [29]…”
Section: Resultsmentioning
confidence: 99%
“…The ability of a carrier to penetrate or fuse through membranes has been characterized by measuring calcein dye leakage from dye-loaded DPPC liposomes [4850]. We have found that this property correlates with AON-mediated gene silencing in cell culture [51].…”
Section: Resultsmentioning
confidence: 99%